2020
DOI: 10.1093/europace/euaa132
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of recurrence of atrial fibrillation within the first 3 months after ablation

Abstract: Aims Freedom from atrial fibrillation (AF) at 1 year can be achieved in 50–70% of patients undergoing catheter ablation. Recurrent AF early after ablation most commonly terminates spontaneously without further interventional treatment but is associated with later recurrent AF. The aim of this investigation is to identify clinical and procedural factors associated with recurrence of AF early after ablation. Methods and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…The ablation of PeAF in elderly women showed the worst outcomes, which indicates that women may require intervention during the early stage of AF (12)(13)(14)(15). To prevent failure of ablation and achieve better outcomes, we recommend intensive screening for AF and aggressive intervention for paroxysmal AF in elderly women.…”
Section: Discussionmentioning
confidence: 99%
“…The ablation of PeAF in elderly women showed the worst outcomes, which indicates that women may require intervention during the early stage of AF (12)(13)(14)(15). To prevent failure of ablation and achieve better outcomes, we recommend intensive screening for AF and aggressive intervention for paroxysmal AF in elderly women.…”
Section: Discussionmentioning
confidence: 99%
“…Not all patients with an early event go on to develop recurrence, however the two are associated to some degree [ 13 ]. More recent studies have shown 90 day recurrence rates of 28% [ 14 ] and one year recurrence rates of 27.6% [ 1 ]. Our data does not reflect outpatient, emergency department, or heart monitor detection of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the most popular academic view is the pulmonary vein potential theory, so the aim of ablation is to isolate the pulmonary vein potential. However, the treatment effect is not ideal, and the 1-year recurrence rate can reach 30-50% (3,4). Furthermore, to minimize the postoperative recurrence rate and improve the quality of life of patients with Af, this study gathers unique insights by using preoperative biological index information.…”
Section: Background and Rationalementioning
confidence: 99%
“…Catheter ablation (CA) is more effective than drug therapy in treating atrial fibrillation (2). However, 30-50% of patients undergoing CA suffer from a recurrence within 1 year of the procedure (3).…”
Section: Introductionmentioning
confidence: 99%